2022
DOI: 10.1128/mbio.01481-22
|View full text |Cite
|
Sign up to set email alerts
|

The Histidine Kinase CckA Is Directly Inhibited by a Response Regulator-like Protein in a Negative Feedback Loop

Abstract: The two-component systems (TCS) in bacteria in its simplest architecture consist of a histidine kinase (HK) and a response regulator (RR). In response to a specific stimulus, the HK is activated and drives phosphorylation of the RR, which is responsible of generating an adaptive response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Phylogenetic analyses have shown that the fla1 genes originated from a horizontal transfer event whereas the fla2 genes are the vertically inherited genes in the α-proteobacteria linage [68]. So far, the Fla2 flagellum has been studied in mutant strains carrying two different mutations, one prevents the expression of Fla1 by removing the gene encoding for the Fla1-master regulator FleQ, and the other, is a gain of function mutation in CckA or a deleterious mutation in its negative regulator Osp [70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses have shown that the fla1 genes originated from a horizontal transfer event whereas the fla2 genes are the vertically inherited genes in the α-proteobacteria linage [68]. So far, the Fla2 flagellum has been studied in mutant strains carrying two different mutations, one prevents the expression of Fla1 by removing the gene encoding for the Fla1-master regulator FleQ, and the other, is a gain of function mutation in CckA or a deleterious mutation in its negative regulator Osp [70][71][72].…”
Section: Introductionmentioning
confidence: 99%